Genetic dissection of NK cell responses - Moussa, Peter; Marton, Jennifer; Vidal, Silvia M.; Fodil-Cornu, Nassima (Frontiers in Immunology, 2013)
The association of Natural Killer cell deficiencies with disease susceptibility has established a central role for NK cells in host defence. In this context, genetic approaches have been pivotal in elucidating and characterizing the molecular mechanisms underlying NK cell function. To this end, homozygosity mapping and linkage analysis in humans have identified mutations that impact NK cell function and cause life-threatening diseases. However, several critical restrictions accompany genetic studies in humans. Studying NK cell pathophysiology in a mouse model has therefore proven a useful tool. The relevance of the mouse model is underscored by the similarities that exist between cell-structure-sensing receptors and the downstream signalling that leads to NK cell activation. In this review, we provide an overview of how human and mouse QTLs have facilitated the identification of genes that modulate NK cell development, recognition and killing of target cells.